2017
DOI: 10.1021/acs.est.6b03720
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Ballasts Enhance Faradaic Efficiency in Closed-Loop, Membrane-Based Energy Systems

Abstract: Aqueous processes for energy storage and conversion based on reverse electrodialysis (RED) require a significant concentration difference across ion exchange membranes, creating both an electrochemical potential and an osmotic pressure difference. In closed-loop RED, which we recently demonstrated as a new means of energy storage, the transport of water by osmosis has a very significant negative impact on the faradaic efficiency of the system. In this work, we use neutral, nonpermeating solutes as "osmotic bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The results from the model calculations indicated that faradaic losses in the battery were mainly due to osmosis which also inhibits the system from returning to its initial state after charging-discharging cycles. With the aim to reduce undesirable osmotic water flux, a non-charged solute (referred to as 'Osmotic Ballast') was added to the dilute electrolyte solution to balance the osmotic pressure between the dilute and concentrated feed solutions[383]. The use of non-charged ballast resulted in a more than 50 % increase in the faradaic energy efficiency of the close-loop concentration battery compared to ballast-free battery operation.Van Egmond et al showed that the thermodynamic efficiency of CGFB increases with increasing current density and decreases with increasing HCC concentration: a maximum value of 75 % was recorded at 0.5 mol kg -1[104].…”
mentioning
confidence: 99%
“…The results from the model calculations indicated that faradaic losses in the battery were mainly due to osmosis which also inhibits the system from returning to its initial state after charging-discharging cycles. With the aim to reduce undesirable osmotic water flux, a non-charged solute (referred to as 'Osmotic Ballast') was added to the dilute electrolyte solution to balance the osmotic pressure between the dilute and concentrated feed solutions[383]. The use of non-charged ballast resulted in a more than 50 % increase in the faradaic energy efficiency of the close-loop concentration battery compared to ballast-free battery operation.Van Egmond et al showed that the thermodynamic efficiency of CGFB increases with increasing current density and decreases with increasing HCC concentration: a maximum value of 75 % was recorded at 0.5 mol kg -1[104].…”
mentioning
confidence: 99%
“…Bipolar membranes with high water permeability would be necessary to allow higher discharge current densities. Another way of increasing the discharge current density without causing delamination to occur could be to include osmotic ballast in the acid and base solution to increase the rate in which water is transported out of the bipolar membrane into solution …”
Section: Resultsmentioning
confidence: 99%
“…Another way of increasing the discharge current density without causing delamination to occur could be to include osmotic ballast in the acid and base solution to increase the rate in which water is transported out of the bipolar membrane into solution. 56 The voltage efficiencies of all experiments, as shown in Figure 4A, are measured to be between 41% and 63%. This is lower compared with other flow batteries and CGFBs.…”
Section: Main Dissipation Sourcesmentioning
confidence: 97%
“…2). Consequently, the system was discharged at a constant current to mimic analogous discharge studies of galvanostatic cycling tests conducted on batteries and concentration gradient flow batteries [[34], [35], [36], [37]]. Constant current discharge experiments were conducted where 1 L of concentrate and diluate were recirculated through the stack until the potential across the stack reversed.…”
Section: Methodsmentioning
confidence: 99%